A BASIC ENGLISH TEXTBOOK IN ENGLISH FOR COMMUNICATION AND LEARNING STRATEGIES FOR NON-ENGLISH STUDY PROGRAMS - Mara Untung Ritonga; Elly Prihasti Wuryuni; Rizki Fadila Nasution (University of Kuningan, 2026)
This study examines the learning strategies of non–English major students and evaluates the feasibility and effectiveness of A Basic Textbook in English for Communication as a communicative instructional resource in higher education. Persistent challenges in students’ speaking performance, including limited fluency, frequent first language reliance, communication anxiety, and avoidance strategies underscore the need for structured and contextually relevant learning materials. The study employed a research and development (R&D) approach adapted from the Borg and Gall model, encompassing needs analysis, textbook design, expert validation, limited field testing, and effectiveness evaluation. Data were collected through expert validation instruments, speaking performance tests, classroom observations, and student response questionnaires. Expert validation results indicated a high level of feasibility, with mean scores ranging from 4.21 to 4.32 across content, pedagogy, and media design aspects. Effectiveness testing showed a significant improvement in students’ speaking performance, with the mean score increasing from 65.4 (pre-test) to 82.7 (post-test). The instructional impact was further supported by a high effect size (Cohen’s d = 1.12), indicating a strong practical effect of the textbook intervention. Improvements were observed across all speaking components, including fluency, accuracy, vocabulary, pronunciation, and interaction. Qualitative findings revealed a notable shift in students’ communication strategies from avoidance behaviors toward more productive strategies such as paraphrasing, self-repair, circumlocution, and clarification requests, reflecting increased confidence and willingness to communicate. Overall, the findings demonstrate that a task-based, communicative English textbook can effectively enhance both linguistic competence and strategic language use among non–English major students in Indonesian higher education.